2021
DOI: 10.5944/openpraxis.13.3.132
|View full text |Cite
|
Sign up to set email alerts
|

Surfing on Three Waves of MOOCs: An Examination and Snapshot of Research in Massive Open Online Courses

Abstract: The purpose of this research is to examine the research that has been done on MOOCs by applying data mining and analytic approaches and to depict the current state of MOOC research. The text mining revealed four broad themes: (I) MOOCs as a mainstreaming learning model in HE, (II) motivation and engagement issues in MOOCs, (III) assessment issues in MOOCs, and (IV) MOOCs for social learning. The social network analysis indicated that MOOCs are a significant aspect of online education and that learning analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…This is borne out by recent reviews (e.g. [1]), but it also ties with the most influential recent literature in this area as measured by citations. For instance, the top two most cited studies are on self-regulated learning [29] [30].…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…This is borne out by recent reviews (e.g. [1]), but it also ties with the most influential recent literature in this area as measured by citations. For instance, the top two most cited studies are on self-regulated learning [29] [30].…”
Section: Resultsmentioning
confidence: 88%
“…In order to make sense of this literature, several reviews have been made [1]. Here we give an overview of these.…”
Section: Mooc Meta-studies and Research Reviewsmentioning
confidence: 99%
“…However, an earlier study reviewing 10 MOOCs reported that even for elderly people participating in MOOCs, there is very limited research on their engagement (Liyanagunawardena, T. R., & Williams, 2016). In a study analysing 633 articles published between 2016 and 2018, it is suggested to focus more on the social justice and widening participation aspects of MOOCs (Bozkurt, 2021). Besides, as a result of a systematic review study including MOOC research between 2009 and 2019, it is reported that, majority of these studies were conducted on data collected through survey and interviews (Zhu et al, 2020) indicating very limited results on analysing MOOC learner behaviours from the MOOC databases.…”
Section: Introductionmentioning
confidence: 99%
“…Early MOOCs emphasized connections between learners and various platforms, such as connectivist MOOCs (cMOOCs) or openness from classrooms to outside the classrooms in extended MOOCs (xMOOCs). However, owing to the growing emphasis on the individual needs of learners and active feedback, various initiatives in MOOCs have been suggested, such as bended MOOCs (bMOOCs), small MOOCs of a small course or social and seamless MOOCs (sMOOCs), small private online course (SPOC), and the mobile MOOCs (MobiMOOCs) ( Bozkurt, 2021 ; Yousef and Sumner, 2021 ).…”
Section: Introductionmentioning
confidence: 99%